Impacto da perda de peso na probabilidade acumulada de sarcopenia aguda em pacientes idosos hospitalizados por covid-19 - Valadão, Thaisa Araujo (2023)
To determine the cumulative probability of acquiring acute sarcopenia in elderly patients hospitalized for COVID-19. Methods: Cross-sectional study carried out between January/2021 and March/2022 in a private hospital in Cuiabá/MT, Central Region of Brazil. The main variable was the cumulative probability of acquiring acute sarcopenia before hospitalization. Acute sarcopenia diagnose was performed using SARC-F ≥4 questionnaire (Strength, Assistance with walking, Rise from a chair, Climb stairs - and Falls), grip strength <20 kg (female) and <35 kg (male) and calf circumference <33 cm (female) and <34 cm (male). The cumulative probability of acquiring acute sarcopenia was determined among the elderly who had or did not have a percentage of weight loss ≥ 5%, over the 14 days of symptoms before hospitalization. Results: A total of 93 elderly people with a median age (IQR) of 71 (66-78) years and 50 (53.8%) males were studied. Twenty-five (26.9%) were diagnosed with acute sarcopenia. Older adults with acute sarcopenia had more myalgia (p=0.034) and greater weight loss ≥5% before hospitalization (p=0.002). The probability of elderly people with COVID-19 acquiring acute sarcopenia was greater for those with weight loss ≥ 5% (46.1 vs. 16.9%; p=0.010; Exp (B)= 4 .01 95%CI 1.33-12.0) when compared to those without this loss. Conclusion: The probability of elderly with COVID-19 acquiring acute sarcopenia, 14 days before hospitalization, was four times higher for those with weight loss ≥ 5%.